Comparative genetics of selected Southern African Mountain zebra (Equus zebra zebra and Equus zebra hartmannae) populations - Harper, Cindy Kim (University of Pretoria, 2013)
Dissertation (MSc (Production Animal Studies))--University of Pretoria, 2004.